Epidemiological surveillance and phylogenetic diversity of Orthohantavirus hantanense using high-fidelity nanopore sequencing, Republic of Korea. - Kyungmin Park; Jongwoo Kim; Juyoung Noh; Seong-Gyu Kim; Hee-Kyung Cho; Kijin Kim; Ye-Rin Seo; Taehun Lim; Seonghyeon Lee; Jaeyeon Lee; Seung In Lim; Young Hoon Joo; et al. (PLoS Neglected Tropical Diseases)
Background Orthohantavirus hantanense (HTNV) poses a substantial global public health threat due to its role in causing hemorrhagic fever with renal syndrome (HFRS). HTNV outbreaks are particularly prevalent in the Gyeonggi and Gangwon Provinces of the Republic of Korea (ROK). This study aimed to evaluate the application of advanced nanopore sequencing and bioinformatics to generate complete genome sequences of HTNV, with the objective of accurately identifying infection sources and analyzing their genetic diversity. Methodology/principal findings In 2022 and 2023, we collected 579 small mammals from 11 distinct locations across Gyeonggi and Gangwon Provinces, as well as in Gwangju Metropolitan City, ROK. Among these, 498 Apodemus agrarius specimens were subjected to an epidemiological survey to investigate HTNV infections. The serological and molecular positivity of HTNV were found to be 65/498 (13.1%) and 17/65 (26.2%), respectively. Furthermore, 15 whole-genome sequences of HTNV were obtained from rodents in Gyeonggi and Gangwon Provinces. We developed a novel amplicon-based nanopore sequencing approach to acquire high-fidelity and precise genomic sequences of HTNV. Genome exchange analysis revealed three reassortant candidates, including heterogeneous L segments, from Paju-si and Yeoncheon-gun in Gyeonggi Province. Conclusion/significance Our findings enhance the resolution of the spatiotemporal genomic surveillance of HTNV by consistently providing new viral sequences and epidemiological data from HFRS-endemic regions in the ROK. This report signifies a notable advancement in nanopore sequencing techniques and bioinformatics, offering a robust platform for genome-based diagnostics and sophisticated phylogenetic analyses of orthohantaviruses, which are essential for public health strategies aimed at controlling HFRS.